1959
DOI: 10.1084/jem.109.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Physical Characteristics of the Heritable Haptoglobin Groups of Human Serum

Abstract: Ultracentrifugal studies of the α2-proteins of normal human serum before and after the addition of hemoglobin have revealed three separate and clearly distinguishable patterns based on the three major serum haptoglobin groups. Isolation of the three haptoglobin hemoglobin complexes disclosed characteristic patterns for each group. The heterozygote was found to possess electrophoretic and ultracentrifugal components not seen in either homozygote. Separation of normal human serum, to which hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1959
1959
1982
1982

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Absorption of the antiserum with Hp 1-1 removes all re activity with the faster Hp 2-1 component; the slower component still reacts but to a lesser degree than do the Hp 2-2 components. Data obtained with ultracentrifugal analysis (17,19) suggest that Hp 2-1 is a hybrid protein (19) differing in molecular weight from both Hp 2-2 and 1-1. The data presented here show that one com ponent of Hp 2-1 is indistinguishable from Hp 1-1, both on the basis of penetrance in the agar gel and immunologic properties.…”
Section: Micro-heterogeneity Of Haptoglobinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Absorption of the antiserum with Hp 1-1 removes all re activity with the faster Hp 2-1 component; the slower component still reacts but to a lesser degree than do the Hp 2-2 components. Data obtained with ultracentrifugal analysis (17,19) suggest that Hp 2-1 is a hybrid protein (19) differing in molecular weight from both Hp 2-2 and 1-1. The data presented here show that one com ponent of Hp 2-1 is indistinguishable from Hp 1-1, both on the basis of penetrance in the agar gel and immunologic properties.…”
Section: Micro-heterogeneity Of Haptoglobinsmentioning
confidence: 99%
“…17 It has been demonstrated with starch gel immunoelectrophoresis that Hp 2-1 is composed of at least two antigenically different components. One of these penetrates to the same degree in the gel as does Hp 1-1; the other component, which is a series of polymers, penetrates slightly farther into the gel than do the Hp 2-2 poly mers.…”
Section: Micro-heterogeneity Of Haptoglobinsmentioning
confidence: 99%
See 1 more Smart Citation
“…All common Hp types have a strong affinity for hemoglobin (Hb); the Hb binding site in Hp appears to be located on the hp,3-chain (4). Early studies on the immunologic characteristics of Hp did not reveal differences among the three phenotypes, or between free and Hb-bound Hp (5,6). Recently, however, with the use of more discriminating antiReceived for publication 2 May 1968. sera both these categories of antigenic differences have been demonstrated by Korngold (7,8) and by Eichmann, Deicher, and Cleve (9).…”
Section: Introductionmentioning
confidence: 99%
“…Family studies showed that the variants are deter mined by two haptoglobin alleles, Hp1 and Hp2 [42], giving the phenotypes Hp 1-1, Hp 1-2 and Hp 2-2. Hp 1-1 behaves as a homo geneous protein in physico-chemical experiments while Hp 1-2 and Hp 2-2 behave like a series of stable polymers [2,3,13,21,29,38]. C o n n e l l , D ix o n and S m it h ie s subjected purified haptoglobin to reductive cleavage and electrophoresis in acid starch gel containing mercaptoethanol and 8 m urea [12,40,41], They showed that all three types of haptoglobin arc composed of two kinds of polypeptide chains: a and ft.…”
Section: Introductionmentioning
confidence: 99%